Inception [videorecording (DVD)] - Nolan, Christopher, 1970-; Gordon-Levitt, Joseph, 1981-; Watanabe, Ken, 1959-; DiCaprio, Leonardo; Hardy, Tom, 1977-; Page, Elliot. 1987-; Cotillard, Marion, 1975-; Murphy, Cillian, 1976-; Berenger, Tom, 1949-; Caine, Michael (Warner Bros. Entertainment : Distributed by Warner Home Video, 2010)
Dom Cobb is the best there is at extraction; stealing valuable secrets inside the subconscious during the mind's vulnerable dream state. His skill has made him a coveted player in industrial espionage, but also has made him a fugitive and cost him dearly. Now he may get a second chance if he can do the impossible; inception, planting an idea rather than stealing one. If they succeed, Cobb and his team could pull off the perfect crime.